The Effect of Integrating Digital Research and Outdoor Learning in STEM Project-Based Learning on Elementary Students’ Creative Thinking Skills - Fitria Wulandari; Saltanat Meiramova; Fika Megawati; Alinda Tiara Ayudya (Jurnal Pendidikan Sains Indonesia, 2026)
Creative thinking is an important 21st-century competency because it enables students to generate original, valuable, and applicable ideas. However, various studies show that this skill among elementary school students is still low, influenced by pedagogical barriers and limited opportunities for divergent thinking. This study aims to analyze the effect of integrating digital research and outdoor learning in STEM Project-Based Learning (STEM-PjBL) on students' creative thinking skills, as well as to measure the magnitude of the effect produced. The study used a pretest–posttest quasi-experimental design with 38 fourth-grade students divided into control and experimental groups. The experimental group received STEM-PjBL learning enriched with digital research and outdoor learning activities, while the control group received STEM learning. The creative thinking skills instruments met the validity and reliability requirements, and the data passed the normality and homogeneity tests. Paired Samples t-test analysis showed that control group experienced a significant increase (p=0.007), with an average difference of 1.105 points. Meanwhile, the experimental group showed a much greater and highly significant increase (p=0.000), with an average difference of 4.263 points. Furthermore, the difference in posttest scores was very significant, with a medium effect on the control group (d=0.34) and a large effect on the experimental group (d=2.38). The intergroup comparison also showed a large effect too (d=1.57). These findings indicate that integrating digital research and outdoor learning in STEM-PjBL had a stronger effect than the control group to strengthen creative thinking skills in aspects of fluency, flexibility, originality, and elaboration in elementary school students.